1998
DOI: 10.1016/s0009-9236(98)90175-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of 3-month intraindividual variability and the influence of sex and menstrual cycle phase on CYP3A activity as measured by phenotyping with intravenous midazolam*

Abstract: Because no significant differences in midazolam clearance were noted between menstrual cycle phases or between sexes, pharmacokinetic and clinical investigations of CYP3A activity in adults may not require stratification on the basis of menstrual cycle phase or sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
89
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 17 publications
9
89
3
Order By: Relevance
“…Plasma midazolam concentrations were analyzed by a liquid chromatography/mass spectrometry/mass spectrometry assay developed by Prevalere Life Sciences, Whitesboro, NY. Details of this procedure are described elsewhere (Kashuba et al, 1998). The linear range of the assay was 25 to 10,000 pg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma midazolam concentrations were analyzed by a liquid chromatography/mass spectrometry/mass spectrometry assay developed by Prevalere Life Sciences, Whitesboro, NY. Details of this procedure are described elsewhere (Kashuba et al, 1998). The linear range of the assay was 25 to 10,000 pg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…The findings from clinical studies have been inconsistent or inconclusive. For example, mean MDZ clearances were greater in women in several investigations, reaching statistical significance in some (Greenblatt et al, 1984;Gorski et al, 1998Gorski et al, , 1999Zhu et al, 2003;Chen et al, 2006c;Chung et al, 2006;Kharasch et al, 2007;Hu et al, 2009), whereas other studies found equivalence (Kashuba et al, 1998;Dresser et al, 2003;Floyd et al, 2003;Gorski et al, 2003;Eap et al, 2004;Chen et al, 2006a) or even insignificantly higher clearances in men (Thummel et al, 1996). Results of the largest-scale investigation (41 women and 58 men) showed that systemic clearances were 30% greater in women, but there was no sex difference for oral MDZ (Kharasch et al, 2007).…”
Section: Introductionmentioning
confidence: 91%
“…Liquid chromatography-tandem mass spectrometry using alprazolam as the internal standard was used. The assay has been described previously (Kashuba et al, 1998;Chung et al, 2006). Pharmacokinetic parameters were analyzed by noncompartmental analysis using WinNonlin version 3.2 (Pharsight Corporation, Mountain View, CA) (Chung et al, 2006).…”
Section: Subjectsmentioning
confidence: 99%